COMBINATION OF BIOCHAR AS AMELIORANT AND VERMICOMPOST IN INCREASING THE YIELD OF RED ONION (Allium ascalonicum L.): KOMBINASI BIOCHAR SEBAGAI AMELIANT DAN VERMIKOMPOST DALAM MENINGKATKAN HASIL TANAMAN BAWANG MERAH (Allium ascalonicum L.) - Rosnina A.G; Nasruddin; Halim Akbar; Hasnan Habib D. Lubis; Usnawiyah, (ROCE : Jurnal Pertanian Terapan, 2025)
Shallots are a horticultural product experiencing a rising demand, both as a culinary seasoning and as materials for the pharmaceutical industry. This research aims to investigate the effectiveness of biochar and vermicompost as soil amendments that can enhance the characteristics of suboptimal land to boost shallot yields. The study employed a factorial RBD with three replications. The first factor involved the dosage of factorial fertilizer with two observed variables: (i) Vermicompost (V0 = control, V1 = 1 kg /). The incorporation of vermicompost had a significant positive impact on plant height, leaf count, bulb quantity, root length, bulb dry weight, and bulb diameter. Conversely, the application of biochar alone significantly influenced plant height, the number of shallot bulbs, as well as the wet and dry weights of the shallot bulbs. The combination of vermicompost and biochar in a 2:1 ratio per plot proved to be the optimal mix for enhancing growth and productivity, thereby increasing the shallot harvest index.